Efektivitas Undang-Undang No. 23 Tahun 2002 Tentang Perlindungan Anak Terhadap Anak Peserta Musabaqah Tilawatil Qur’an Ke-56 Tahun 2022 di Kabupaten Deli Serdang - Rio Bayu Riansyah Harahap; Ali Akbar (UNES Law Review, 2023)
This article aims to find out whether Law No. 22 of 2002 is effective or not in protecting children whose parents force them to win MTQ activities. This research is empirical juridical research, using a legal sociology approach. Obtained using an interview data collection instrument with some of the parents of the 56th MTQ participants at the Deli Serdang Regency level in 2022, Caravan, Hamparan Perak District. The research results show that Law No. 23 of 2002 has not been effective in protecting children from being forced by their parents to win MTQ activities. There are still some parents of participants who require their children to win just for happiness and there are also parents who have other intentions, namely requiring their children to win to fulfill the needs of the prize. This is very contrary to the initial aim of holding MTQ and Law No. 23 of 2002 is not effective enough to address the problem of child protection for MTQ participants.